An Ultrasensitive Label-Free Fluorescent Aptasensor Platform for Detection of Sulfamethazine - Wang, Yarong (Int J Nanomedicine, 2021)
PURPOSE: Sulfamethazine (SMZ) exposed in the environment can enter the human body through the food chain and pose a serious threat to human health. Therefore, it is important to develop a rapid and sensitive method for detecting SMZ in environmental samples. In order to fastly and quantitatively detect SMZ in environmental samples, we developed a label-free fluorescent aptasensor based on specific aptamer (SMZ1S) and fluorescence resonance energy transfer (FRET) between gold nanoparticles (AuNPs) and rhodamine B (RhoB). METHODS: In the absence of SMZ, SMZ1S was adsorbed on the surface of AuNPs, which led to dispersion of the AuNPs in high concentration saline solution, thus effectively quenching the fluorescence of RhoB. With the increase of the SMZ concentration, the specific binding of SMZ1S and SMZ led to the aggregation of AuNPs in the presence of NaCl, which reduced the quenching of RhoB fluorescence and increased the fluorescence intensity. The sensitivity and linearity curve of the label-free fluorescent aptasensor were determined with different concentrations of sulfamethazine standard solutions. The specificity of this fluorescent aptasensor was determined by replacing sulfamethazine with different antibiotics. In addition, the actual water and soil samples were spiked and recovered. RESULTS: Under optimized conditions, the proposed fluorescent aptasensor demonstrated a good linear detection of SMZ in binding buffer from 1.25 ng mL(−1) to 40 ng mL(−1) and the limit of detection was 0.82 ng mL(−1). The spiked recoveries for SMZ were 94.4% to 108.8% with a relative standard deviation of 1.8–10.3% in water and soil samples, respectively. CONCLUSION: The label-free fluorescent aptasensor investigated in the current study is a promising tool to detect and quantify SMZ in water and soil samples.